A quest for the unknown : a biography of late Rev. Dr. M.A. Thomas, founder director of Ecumenical Christian Centre - Kurien, M (Delhi Tiruvalla : CSS, 2002)
Biography of a Christian social activist from Kerala, India
Keywords: Thomas, M. A. -- (Madathethu Abraham) Christian biography -- India -- Kerala. Social reformers -- India -- Kerala -- Biography. Kerala (India) -- Biography. Christian biography. Social reformers. India -- Kerala